2016
DOI: 10.1126/scitranslmed.aai8336
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of human neutralizing antibodies isolated from a patient infected with Zika virus

Abstract: The 2015-2016 outbreak of Zika virus (ZIKV) disease has affected many countries and is a major public health concern. ZIKV is associated with fetal microcephaly and neurological complications, and countermeasures are needed to treat and prevent ZIKV infection. We report the isolation of 13 specific human monoclonal antibodies from a single patient infected with ZIKV. Two of the isolated antibodies (Z23 and Z3L1) demonstrated potent ZIKV-specific neutralization in vitro without binding or neutralizing activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
223
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(234 citation statements)
references
References 56 publications
(59 reference statements)
3
223
0
5
Order By: Relevance
“…Maturation of virus particles occurs during virus egress via the secretory pathway, where furin in the Golgi apparatus cleaves prM, releasing the pr peptide as the virus reaches neutral pH upon exit from the cell (14). The E protein is the major target for neutralizing antibodies, and monoclonal antibodies against all 3 E protein domain (DI, DII, and DIII) target epitopes have been found (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Maturation of virus particles occurs during virus egress via the secretory pathway, where furin in the Golgi apparatus cleaves prM, releasing the pr peptide as the virus reaches neutral pH upon exit from the cell (14). The E protein is the major target for neutralizing antibodies, and monoclonal antibodies against all 3 E protein domain (DI, DII, and DIII) target epitopes have been found (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Interestingly, the proportions of ZIKV-specific MAbs in the MAb groups differ. Among the 153 tested MAbs, 63 specifically bind to ZIKV E protein (E MAbs) (8)(9)(10)(11)(12)(13)(14), while 45 of 70 MAbs that convey 50% inhibition of the virus at a concentration of Ͻ1 g/ml are specific to ZIKV (8)(9)(10)(11)(12)(13)(14). The proportion of ZIKV-specific MAbs is further increased in focusing on the MAbs with in vivo protective efficacy.…”
mentioning
confidence: 99%
“…Two other monoclonal antibodies showed postexposure protection in mice against Zika virus infection [77]. Isolation of 13 specific human monoclonal antibodies from a single patient infected with ZIKV has been reported.…”
Section: Antibody-based Therapeuticsmentioning
confidence: 99%
“…Isolation of 13 specific human monoclonal antibodies from a single patient infected with ZIKV has been reported. Two of the isolated antibodies (Z23 and Z3L1) demonstrated potent ZIKV-specific neutralization in vitro without binding or neutralizing activity against strains 1 to 4 of DENV, the closest relative to ZIKV [77]. Structural studies revealed that Z23 and Z3L1 bound to tertiary epitopes in envelope protein domain I, II, or III, indicating potential targets for ZIKV-specific therapy [77].…”
Section: Antibody-based Therapeuticsmentioning
confidence: 99%